Template Assisted Fabrication of Ciprofloxacin-Imprinted Polymers for Removal of Ciprofloxacin - Rashid, Mahmood; Showkat Ahmad, Bhawani; Rachel Marcella, Roland; Syed Rizwan, Shafqat; Nadeem A., Khan (John Wiley & Sons Ltd, 2026)
The study presents the development of highly specific molecular imprinted polymers for adsorptive removal of ciprofloxacin (CIP) from aqueous media. Ciprofloxacin is one of the commonly used antibiotics which is usually found in effluents due to its inadequate removal from wastewater by conventional treatment methods. In aquatic settings, its persistence contributes to antibiotic resistance and hence poses different risks for aquatic organisms. In this study, the removal behavior of CIP designated as a model contaminant was investigated using state of the art Molecular Imprinting Technology (MIT). Herein, the precipitation polymerization approach was used to synthesize a series of ciprofloxacin molecular imprinted polymers (CIP-MIPs) by changing the solvent ratios and volume of functional monomers. Optimized CIP3-MIP and CIP6-MIP were obtained while using higher concentration ratios of ethanol, acetonitrile, and dimethyl sulfoxide. Prepared CIP-MIPs were characterized to investigate their structural interactions using the FTIR study. Surface analysis of CIP-MIPs as well as non-imprinted polymers (NIPs) was performed employing SEM and the prepared polymers exhibited porous surface having particle size 0.07μm. EDX studies confirmed the elemental composition of CIP-MIPs. Thermal properties of CIP, CIP-MIPs and NIPs were analyzed using TGD/DTG. Moreover, CIP-MIPs were employed to remove CIP from aqueous media using well established rebinding parameters including initial CIP concentration, adsorbent dosage of CIP-MIPs, pH and agitation rate. The findings of batch binding studies illustrated that optimized CIP3-MIPs and CIP6-MIPs were able to rebind about 99.1% and 97.24%, respectively of CIP at initial CIP concentration 20ppm, polymer dosage of 0.3 g at pH7 and the agitation speed of 150 rpm. The imprinting factor of 1.73 and 1.699 were an indicator towards higher selectivity of CIP3-MIP and CIP6-MIP towards CIP, respectively. In addition, minimum loss of only 2.05% and 2.84% in the removal efficiency within 10 sequential cycles of adsorption–desorption process proved that CIP3-MIPs and CIP6-MIPs might be employed as the cost effective and suitable adsorbents for the removal of CIP from water bodies.